116 Meta-analysis of 3 trials: the effect a novel consensus bacterial 6-phytase variant on phosphorus digestibility and retention in piglets fed inorganic phosphate free diets. (30th November 2020) - Velayudhan, Deepak; Hardy, Rachael; Marchal, Leon; Dersjant-Li, Yueming
Abstract: A meta-analysis was conducted to investigate the effect of a novel consensus bacterial 6-phytase variant on apparent total tract digestibility (ATTD) of phosphorus (P) and P retention in piglets (initial body weight of 9.6 ± 1.8 kg). Database was constructed using 3 studies (unpublished), contributing 189 data points. All studies had a positive control (PC) diet with adequate levels of calcium (Ca; 0.57–0.85%) and digestible P (0.25–0.29%), a negative control (NC) diet with low Ca and digestible P levels (total removal of inorganic P). Piglets were fed a corn or wheat soybean meal-based diet with rice bran or sunflower meal for 7–10 d, followed by 4 d fecal and urine collection. Total analyzed Ca, total P, calculated digestible P and phytate P levels in NC varied from 0.48 to 0.79%, 0.37 to 0.40%, 0.16 to 0.18%, and 0.24 to 0.28%, respectively, among studies. The NC diet was supplemented with a novel consensus bacterial 6-phytase variant (PhyG) or a commercial Buttiauxella sp. phytase (PhyB), at 500 and 1, 000 FTU/kg. Data were analyzed using Mixed Model by JMP 14.0. Addition of both phytases improved (P < 0.05) ATTD P compared to NC diets. The NC reduced digestible P (g/kg) vs PC, both phytases showed greater (P < 0.05) digestible P (g/kg) when compared to NC and recovered to the level of PC. Digestible P improvement (g/kg) over NC showed a significant phytase effect, where PhyG supplementation had 17% greater (P < 0.05) digestible P improvement when compared to PhyB. Phosphorus retention improved (P < 0.05) with phytase supplementation, with 1, 000 FTU/kg showing greater (P < 0.05) P retention when compared to 500 FTU/kg. It was concluded that both PhyG and PhyB are efficient in improving ATTD P and P retention, PhyG showed greater digestible P improvement when compared to PhyB, and 1, 000 FTU/kg showed greater effect than 500 FTU/kg.